A framework for the implementation of e-procurement practices in the South African public sector - Mothibi, Gloria Mokgalagadi (Vaal University of Technology, 2020)
The use of technology in supply chain management has increased over the years. Procurement is one of the primary supply chain management areas where the use of technology has gained momentum. This has been realised through the use of e-procurement systems. However, the adoption and implementation of e-procurement can be achieved more effectively if available models of technology adoption are taken into consideration. This study tested a conceptual framework integrating the Technology Acceptance Model (TAM) and the Unified Theory of the Acceptance and use of Technology (UTAUT) in the implementation of e-procurement practices in the South African public sector. Although there are several studies that have focused on procurement in the public sector in South Africa, there is no evidence of studies that extended the use of the TAM and the UTAUT within the public sector in South Africa. This study was conducted to fill this gap by proposing a framework combining the TAM and UTAUT and modelling their role in the adoption of e-procurement in the public sector. The study adopted a survey design and a quantitative research approach was used to evaluate relationships between different variables. The final sample for this study consists of 263 supply chain management (SCM) practitioners drawn from the public sector in the Gauteng Province, South Africa. A self-completion survey questionnaire was used to gather data to measure the eight constructs of the TAM and UTAUT. An Exploratory Factor Analysis (EFA) procedure was performed to assess the factor structure of the data collected in the study. Descriptive statistics were applied to examine the demographic profile of respondents and the perceptions of respondents towards the research constructs. Pearson correlations were used to test relationships and regression analysis was used to test the hypotheses. In the EFA, two new factors, labelled as Personal Competence and External Assistance, were identified. The results of the hypotheses tests showed that five factors, namely: perceived use, self-efficacy, facilitating conditions, personal competence and external assistance significantly predicted attitudes towards the use of e-procurement systems. However, perceived ease of use was statistically insignificant. The results further show that attitudes towards system use significantly predict behavioural intention, which in turn significantly influences actual e-procurement system use. The theoretical framework fusing the TAM and UTAUT models provides useful insights for other researchers and adds valuable knowledge to the factors that might contribute to the adoption of e-procurement in the South African public sector. The study further makes significant contributions to SCM professionals in the public sector. It reiterates the challenges faced in SCM in the public sector and then demonstrates how the adoption of e-procurement could improve the system, while reducing service delivery inequality. By indicating the factors either promoting or impeding the adoption of e-procurement in the public sector, the study provides practitioners and other decision makers in SCM with suggestions on how to facilitate more rapid adoption and circumvent the influence of irrelevant factors. Among other things, the study recommends that to improve the adoption and continued use of e-procurement systems in the public sector in the Gauteng Province, it is necessary to customise the e-procurement system to ensure that it responds to the needs of users. In addition, it is important to increase the confidence and competence of users of the systems, providing the relevant technical infrastructure and support to users in order to positively influence their attitudes and behavioural intention towards the use of e-procurement systems.
Ph. D. (Department of Business Administration, Faculty of Management Sciences), Vaal University of Technology.
Keywords: E-procurement; Public Sector, South Africa; Supply chain management; Technology Acceptance Model (TAM); Unified Theory of the Acceptance and Use of Technology (UTAUT); Dissertations, Academic -- South Africa; Electronic commerce -- South Africa; Business logistics -- South Africa -- Electronic information resources; Purchasing -- South Africa -- Electronic information resources